Pulmonary and cardiac involvement in patients with rheumatoid arthritis and ankylosing spondylitis - Tekeli, Ahmet Hüsrev (The European Research Journal, 2023)
Objectives: Our aim is to study the disease activity status, laboratory data and to determine the frequency of cardiac and pulmonary findings in patients with Rheumatoid arthritis (RA) and ankylosing spondylitis (AS). Methods: Forty-five AS patients and 78 RA patients took part in the study. The C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), albumin, creatinine, ALT, leukocyte, neutrophil ratio, hemoglobin, platelet, rheumatoid factor (RF), and anti-cyclic citrullinated peptide (anti-CCP) levels were measured. In addition, the patients’ thoracic computed tomography, high-resolution computed tomography (HRCT), echocardiography (ECHO), and pulmonary function test (PFT) results were evaluated. Disease activity was assessed with the Disease Activity Score-28 (DAS-28) in RA patients, whereas the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was used in patients with AS. Results: The relationship between the anti-CCP value and gender was significant in RA patients. Significant differences were present between gender and hemoglobin value in RA and AS patients, whereas no significant differences were determined between CRP, ESR, platelet, and DAS-28 values. There was a significant difference between RF and ESR values in RA patients, whereas no significant difference was present between CRP, leukocyte, DAS-28, hemoglobin, and platelet values. Pulmonary involvement was determined in 35.7% of RA patients and 4.2% of AS patients. The difference between these was statistically significant. Conclusions: The most common pulmonary involvement is millimetric nonspecific nodule and the most common lesion among ECHO findings was left ventricular diastolic dysfunction in RA and AS patients. In RA, no significant difference was determined between PFT and DAS-28 results, as a result, the disease activity will not directly indicate pulmonary involvement.